The Role of Child Abuse Experience in College Students' Adaptation at University - Khairunnisa, Nadhira; Islam, Azizah Fajar (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
College adjustment is a challenge for new students, especially for those with childhood abuse experiences. This study aims to examine the effect of child abuse experiences on college adjustment. The method used is quantitative with simple linear regression analysis involving 184 freshmen with child abuse experiences. The results show that child abuse experiences negatively affect college adjustment. Students with such experiences tend to face difficulties in emotional, social, academic, and institutional adjustment. These findings confirm that past experiences contribute to difficulties in adjustment and highlight the importance of psychosocial interventions in higher education institutions. Colleges are encouraged to provide psychological support services for students with child abuse backgrounds to help them adapt academically and socially.